2006
DOI: 10.1089/sur.2006.7.379
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Antibiotic Use in Open Fractures: An Evidence-Based Guideline

Abstract: The data support the conclusion that a short course of first-generation cephalosporins, begun as soon as possible after injury, significantly lowers the risk of infection when used in combination with prompt, modern orthopedic fracture wound management. There is insufficient evidence to support other common management practices, such as prolonged courses or repeated short courses of antibiotics, the use of antibiotic coverage extending to gram-negative bacilli or clostridial species, or the use of local antibi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
119
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 217 publications
(125 citation statements)
references
References 119 publications
(110 reference statements)
2
119
0
4
Order By: Relevance
“…The benefits of prophylactic antibiotic use against Gram positive bacteria have since been supported by other series. [11][12][13] While research supports the benefits of prophylactic antibiotics that target Gram positive bacteria, there is insufficient evidence to support the prophylactic use of Gram negative antibiotics. 9,13,14 As Gram negative bacteria become more prevalent in open fracture infections, including Acinetobacter baumannii and Pseudomonas aeruginosa, research addressing the prophylactic benefits of Gram negative antibiotics will become increasingly important.…”
Section: Discussion Current Concepts In Open Fracture Care and Infectmentioning
confidence: 99%
See 1 more Smart Citation
“…The benefits of prophylactic antibiotic use against Gram positive bacteria have since been supported by other series. [11][12][13] While research supports the benefits of prophylactic antibiotics that target Gram positive bacteria, there is insufficient evidence to support the prophylactic use of Gram negative antibiotics. 9,13,14 As Gram negative bacteria become more prevalent in open fracture infections, including Acinetobacter baumannii and Pseudomonas aeruginosa, research addressing the prophylactic benefits of Gram negative antibiotics will become increasingly important.…”
Section: Discussion Current Concepts In Open Fracture Care and Infectmentioning
confidence: 99%
“…One study has suggested that antibiotic treatment should be continued for 3 days after initiation, 31 while another study argues that 24 h is no less effective than 72 h. 32 Currently, authors advise that antibiotic treatment should be continued for at least 24 h, and may be continued for up to 72 h. 9,13,14 A concern with longer antibiotic administration times (i.e., 72 h) is that the increased exposure may promote antibiotic resistance among the bacterial populations, which has been shown to occur in some cases. 9,13 Further research will be required to provide definitive responses to these concerns.…”
Section: Discussion Current Concepts In Open Fracture Care and Infectmentioning
confidence: 99%
“…However, surgical site infection (SSI), a devastating complication associated with orthopaedic implants, can prolong the length of hospital stay and dramatically increase the medical costs [16,20]. To minimise SSI occurrences, perioperative prophylactic antibiotics have been routinely used for all patients undergoing ORIF procedures.…”
Section: Introductionmentioning
confidence: 99%
“…In line with these observations, it has been shown that cultures obtained at initial debridements correlate poorly with later infections, which is why we only included cultures from patients that were clinically infected, and not cultures from day zero to two [22,23]. Thus, antibiotic treatment should be broad, target both Gram positive and negative organisms, and the risk of generating resistance should be small [13][14][15][16]. The risk can be further reduced by using antibiotics that are renally excreted with minor impact on the normal flora, as proposed by Sullivan et al [21].…”
Section: Discussionmentioning
confidence: 91%